Perancangan Sistem Informasi PPDB (Penerimaan Peserta Didik Baru) Berbasis Website Pada SMPK Pa Van Der Steur Di Bekasi - Setyowanti, Amanda Dwi; Fitriani, Yuni; Indrarti, Wahyu; Rahayu, Luci Kanti (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2025)
The rapid development of technology in the digital era, including in the field of education, encourages continuous efforts to improve the effectiveness and efficiency in managing academic and administrative activities. The process of new student admissions that is still carried out manually has caused various problems, such as long queues, the risk of data recording errors, lost documents, and a lack of transparency of information. This research aims to study the existing registration system, design an effective online registration system based on a website according to the needs, and compile detailed documentation of the system design. The software development method used in this research is the waterfall model. To collect the necessary data, the author conducted data collection activities using several methods, including observation, interviews, and literature studies. The result of this research is a design of a web- based information system for new student admissions that can improve time efficiency, facilitate the registration and selection process, support structured data storage, and provide easy access to information for prospective students and parents. Based on the analysis and system design described, it is expected that this system will provide time efficiency in the registration process and assist administrators in managing data.